Test–Retest Reliability of Common Measures of Eating Disorder Symptoms in Men Versus Women. (April 2019) - Forbush, Kelsie T.; Hilderbrand, Lindsay A.; Bohrer, Brittany K.; Chapa, Danielle A. N.
Approximately 10% to 30% of individuals with eating disorders (EDs) are male, yet because measures often have not been tested among male participants, it is unclear whether the psychometric properties of ED measures are equivalent between sexes. The purpose of this study was to compare the test–retest reliability of common ED measures in men versus women. Participants ( N = 227; 58.1% female) completed self-report measures of body dissatisfaction, restrained eating, disinhibited eating, bulimic symptoms, and desire-for-muscularity at baseline and 2-to-4 weeks later. Intraclass correlations were used to compute retest correlations. Spearman's rho was used to compute retest correlations for skewed and kurtotic variables. We compared 95% confidence intervals for intraclass correlation coefficients to determine whether measures differed in reliability between sexes. Most ED measures had at least acceptable test–retest reliabilities. However, few measures of disinhibited and binge eating demonstrated good reliability in men. Results highlight the utility of several ED measures for assessing symptom change over time, and the need for additional research to identify and correct for sources of gender unreliability among ED self-report measures in men—particularly for assessing constructs that include binge-eating behavior.